Test of Various Carrier Materials Against Viability and Conidia Density in Some Liquid Biopesticides of Entomopathogenic Fungi - Unun Triasih; dina agustina; mutia erti dwiastuti; susi wuryantini (Universitas Djuanda Bogor, 2019)
Indonesia is a country that has a large biological diversity but has not been fully utilized for agriculture. The effectiveness of biological agents in controlling pests and plant diseases still needs further investigation, one of which is the use of entomopathogenic fungi as biopesticides. The purpose of this study was to determine the effect of storage on the viability and density of conidia in several entomopathogenic fungi; Beauveria bassiana, Metarhizium anisopliae, Paecilomyces. This study used 5 entomopathogenic fungi isolates, 2 Beauveria bassiana isolates (JBG and JBR), 2 Metarhizium anisopliae isolates (JBG and UST), 1 Paecilomyces. Biopesticide carrier material consisted of 6 carrier materials, namely soybean decoction waste, soy washing waste, Potato Dextrose Agar, tapioca waste, rice waste, rice washing waste and coconut water. Biopesticides have been made one year before and the viability and complexity of the conidia is re-examined one year later. From the observations of conidial density, the best was found in Beauveria bassiana JBG liquid biopesticide of 4.8 x 10 x conidia / ml from the initial density of 3.4 x 10⁸ / ml in the soybean decoction (RK) carrier material. The highest viability was found in JBG Metharizium anisopliae on soybean washing waste material by 14%. Key words: Conidia viability, conidial density, entomopathogenic fungi